MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA PEMBELAJARAN GENIALLY PADA SISWA KELAS V - Yusuf, Diva Quitza; Husain, Rustam I; Aries, Nur Sakinah; Marshanawiah, Andi; Mahniar, Ade (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aimed to improve fifth-grade students’ mathematics learning outcomes through the use of Genially as a digital learning medium at SDN 3 Bulango Utara. The research employed a Classroom Action Research (CAR) design conducted in a cyclical and systematic manner, with each cycle consisting of planning, action, observation, and reflection stages. The research subjects were 12 fifth-grade students, comprising 7 female students and 5 male students. Data were collected through learning achievement tests, observations of teacher and student activities, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The results indicated a significant improvement in students’ mathematics learning outcomes after the implementation of Genially-based learning media. In the pre-action stage, only 25% of students achieved the minimum mastery criterion (score ≥ 75). Following the implementation of the actions, learning mastery increased to 58.33% in Cycle I and further improved to 83.33% in Cycle II. In addition, students’ learning activities showed improvement from a fair category to a very good category. These findings demonstrate that the use of Genially as a learning medium is effective in improving mathematics learning outcomes of fifth-grade elementary school students. ABSTRAK Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika siswa kelas V SDN 3 Bulango Utara melalui penggunaan media pembelajaran Genially. Penelitian ini menggunakan model Penelitian Tindakan Kelas (PTK) yang dilaksanakan secara bertahap, dengan setiap siklus meliputi tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian terdiri atas 12 siswa, yaitu 7 siswa perempuan dan 5 siswa laki-laki. Data dikumpulkan melalui tes hasil belajar, observasi aktivitas guru dan siswa, serta dokumentasi, kemudian dianalisis menggunakan teknik deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan adanya peningkatan hasil belajar matematika siswa setelah penerapan media Genially. Pada kondisi awal, hanya 25% siswa yang mencapai Kriteria Ketuntasan Minimal (KKM ≥ 75). Setelah pelaksanaan tindakan, ketuntasan belajar meningkat menjadi 58,33% pada siklus I dan mencapai 83,33% pada siklus II. Selain itu, aktivitas siswa dalam pembelajaran juga mengalami peningkatan dari kategori cukup menjadi kategori sangat baik. Dengan demikian, penggunaan media pembelajaran Genially terbukti efektif dalam meningkatkan hasil belajar matematika siswa kelas V SDN 3 Bulango Utara.